Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = 2x + 3 \)[/tex], we need to follow a systematic process. An inverse function essentially "undoes" what the original function does.
Here are the steps to find the inverse function:
1. Express the function as an equation in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x + 3 \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to create the equation of the inverse:
[tex]\[ x = 2y + 3 \][/tex]
3. Solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ x = 2y + 3 \][/tex]
Subtract 3 from both sides:
[tex]\[ x - 3 = 2y \][/tex]
Divide both sides by 2:
[tex]\[ y = \frac{x - 3}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{x - 3}{2} \][/tex]
Let's compare with the given options and choose the correct inverse function:
1. [tex]\( f^{-1}(x) = -\frac{1}{2}x - \frac{3}{2} \)[/tex]
2. [tex]\( f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \)[/tex]
3. [tex]\( f^{-1}(x) = -2x + 3 \)[/tex]
4. [tex]\( f^{-1}(x) = 2x + 3 \)[/tex]
We can see that the correct inverse function [tex]\( \frac{x - 3}{2} \)[/tex] can be rewritten as:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
So the correct option is:
[tex]\[ \boxed{f^{-1}(x) = \frac{1}{2}x - \frac{3}{2}} \][/tex]
Here are the steps to find the inverse function:
1. Express the function as an equation in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x + 3 \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to create the equation of the inverse:
[tex]\[ x = 2y + 3 \][/tex]
3. Solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ x = 2y + 3 \][/tex]
Subtract 3 from both sides:
[tex]\[ x - 3 = 2y \][/tex]
Divide both sides by 2:
[tex]\[ y = \frac{x - 3}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{x - 3}{2} \][/tex]
Let's compare with the given options and choose the correct inverse function:
1. [tex]\( f^{-1}(x) = -\frac{1}{2}x - \frac{3}{2} \)[/tex]
2. [tex]\( f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \)[/tex]
3. [tex]\( f^{-1}(x) = -2x + 3 \)[/tex]
4. [tex]\( f^{-1}(x) = 2x + 3 \)[/tex]
We can see that the correct inverse function [tex]\( \frac{x - 3}{2} \)[/tex] can be rewritten as:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
So the correct option is:
[tex]\[ \boxed{f^{-1}(x) = \frac{1}{2}x - \frac{3}{2}} \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.